USE OF PERT (PROGRAM EVALUATION AND REVIEW TECHNIQUE) AND PDM (PRECEDENCE DIAGRAMMING METHOD) IN ORGANIZING MODERN VEGETABLE SEEDLING PRODUCTION - Ljiljanić, Nikola; Rajić, Zoran; Paunović, Tamara (Economics of Agriculture, 2022)
Propagation of quality vegetable seedlings is a key of successful vegetable production in an open field and in protected areas. The research is aimed at the production process itself, analyzing it from technological and organizational aspects. Based on a detail calculation of time, means and costs, the researchers obtained the duration of production in days, regarding the propagation of pepper, tomato, cabbage and lettuce seedlings, taking into consideration different technological requirements of crops, ripening time, delivery time and an optimal use of the propagation area. The use of the Program Evaluation and Review Technique required more attention when making a production plan, resulting in the introduction of activities, the realization of which required only the ﬂow of time to harmonize the monitoring of real activities. By using the Precedence Diagramming Method this problem was overcome with predefining the type of relationship between the interdependent activities (Finish-to-Start, Finish-to-Finish, Start-to-Start, and Start-to-Finish).